Field performance and fruit quality of strawberry genotypes under subtropical climate - Rahman, M Moshiur; Rahman, MM; Hossain, MM; Mian, MA Khaleque; Khaliq, QA (Bangladesh Journal of Agricultural Research, 2015)
Thirteen strawberry genotypes collected from different sources were evaluated at the Fruit Research Field of Pomology Division, HRC, BARI, Gazipur, Bangladesh during the winter season of 2009-2010 and 2010-2011 for yield, yield contributing characters and nutrient components of fruit. Among the 13 genotypes studied, the plants of FA 005 produced the maximum number of fruits (43.50 plant-1) followed by FA 006 and FA 007 (37.50 plant-1), while FA 009 and FA 013 produced the minimum number of fruits (9.00 plant-1). The heaviest fruits were produced by FA 006 (18.73 g) followed by FA 007 (17.40 g) and FA 005 (16.96 g) which were statistically similar, while the lightest fruit was found in FA 014 (5.11 g). The fruit yield plant-1 of different genotypes varied from 52.00 to 737.70 g and plants of FA 005 produced the maximum yield followed by FA 006 (702.30 g plant-1) and these were significantly higher than those of others. The minimum yield plant-1 was recorded in FA 013 and FA 014. The TSS content was highest in FA 007 (8.50 %) followed by FA 017 (8.17 %), whereas the lowest was in FA 009 (6.33 %). The TSS to acid ration was maximum in FA 006 (11.32) followed by FA 017 (11.24), FA 007 (10.80) and FA 005 (10.62), while the lowest was in FA 011 (6.95). The sugar to acid ratio significantly ranging from 3.60 to 5.98, and it was maximum in FA 006 (5.98). Plants of FA 005 contained the maximum amount of ascorbic acid (77.33 mg 100g-1) followed by FA 006 (76.00 mg 100g-1), while the minimum in FA 010 (53.00 mg 100g-1). Bangladesh J. Agril. Res. 40(1): 137-151, March 2015